2018
DOI: 10.1016/s2215-0366(18)30184-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy in clozapine-resistant schizophrenia (FOCUS): an assessor-blinded, randomised controlled trial

Abstract: SummaryBackgroundAlthough clozapine is the treatment of choice for treatment-refractory schizophrenia, 30–40% of patients have an insufficient response, and others are unable to tolerate it. Evidence for any augmentation strategies is scarce. We aimed to determine whether cognitive behavioural therapy (CBT) is an effective treatment for clozapine-resistant schizophrenia.MethodsWe did a pragmatic, parallel group, assessor-blinded, randomised controlled trial in community-based and inpatient mental health servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 39 publications
0
71
1
3
Order By: Relevance
“…This finding may be explained by the fact that treatment-resistant symptoms are more difficult to treat, and therefore a CBT intervention can bring only a lower improvement compared to that of other patients. A trial on clozapine-resistant patients receiving CBT, published after the date of our search, reported responders’ rates that are slightly higher than the ones that we found (46 and 7% for the 20 and 50% PANSS total reduction of symptoms, respectively) [ 24 ].…”
Section: Discussionmentioning
confidence: 80%
“…This finding may be explained by the fact that treatment-resistant symptoms are more difficult to treat, and therefore a CBT intervention can bring only a lower improvement compared to that of other patients. A trial on clozapine-resistant patients receiving CBT, published after the date of our search, reported responders’ rates that are slightly higher than the ones that we found (46 and 7% for the 20 and 50% PANSS total reduction of symptoms, respectively) [ 24 ].…”
Section: Discussionmentioning
confidence: 80%
“…The recently published FOCUS trial (Morrison et al, 2018) examined the effectiveness of CBT over a period of 9 months (plus later booster sessions) v. TAU in 487 patients with clozapine-resistant schizophrenia. As well as being very large, this trial was well-conducted, employed randomization by remote allocation and assessor blinding (with measures taken to address accidental breaking), and analysis was by means of a modern equivalent of intention-to-treat (White et al, 2011).…”
Section: Cbt For Relapsementioning
confidence: 99%
“…Hutton and Taylor (2014) meta-analyzed six trials using CBT in individuals at risk of developing psychosis, and found evidence that it was effective in reducing the transition rate at 6, 12, and 18 months [6 months: RR 0.47 (95% CI 0.27-0.82), six studies; 12 months: RR 0.45 (95% CI 0.28-0.73), six studies; 18-24 months: RR 0.41 (95% CI 0.23-0.72), four studies]. This meta-analysis included two large, well-conducted multicenter trials (n = 288, Morrison et al, 2012 andn = 206, van der Gaag et al, 2012); the former failed to find a significant difference in transition frequency but the latter found a significant (55%) reduction.…”
Section: Can Cbt Prevent Transition To Psychosis?mentioning
confidence: 99%
“…Die Kombination von kognitiver Verhaltenstherapie und antipsychotischer Medikation wurde bisher kaum in einer behandlungsresistenten Population untersucht. In einer großen Studie mit 487 Teilnehmern wurde der Effekt von kognitiver Verhaltenstherapie zusätzlich zur medikamentösen Therapie über einen Zeitraum von fast 2 Jahren untersucht [43]. Eingeschlossen wurden nur Teilnehmer, die sich unter einer Behandlung mit Clozapin nicht ausreichend verbessert hatten oder diese nicht vertragen hatten.…”
Section: Kognitive Verhaltenstherapieunclassified